About the use of time on argumentative systems - Cobo, María Laura (2005)
There are many areas in Computer Science where time plays an important role. Artificial Intelligence is one of them. In this particular area Defeasible Logic Programming (DeLP) was developed to cope with incomplete and potentially inconsistent information. This formalism combines results from Logic Programming and Defeasible Argumentation. DeLP in particular provides the possibility of representing defeasible information in a declarative way and a defeasible argumentation inference mechanism to warrant conclusions. Although this formalism and Defeasible logic programming in general are very useful has left apart an issue that is crucial on several kind of problems, namely time. There are also many developments that face temporal reasoning, in particular Event Calculus, but non of them consider defeasible information or what to do if we have incomplete or not completely reliable information. In this work we try to attempt an exploration of a possible combination of these two reasoning areas, temporal and defeasible.